2017
DOI: 10.1111/apt.13939
|View full text |Cite
|
Sign up to set email alerts
|

Complications of percutaneous liver biopsy with Klatskin needles: a 36‐year single‐centre experience

Abstract: Background Liver biopsy is the gold standard in evaluating liver diseases but is susceptible to complications. Safety data on aspiration needle biopsies remains limited. Aim To evaluate the safety of percutaneous liver biopsy performed with Klatskin needle. Methods Clinical and biochemical data were retrospectively retrieved from sequential subjects who underwent liver biopsy with Klatskin needle from 1978 to 2015. Subjects with complications underwent thorough chart reviews for hospital course. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 40 publications
(69 reference statements)
3
48
0
2
Order By: Relevance
“…A recent large study analyzing 3,357 percutaneous liver biopsies performed with Klatskin needle in patients with liver disease (including advanced CLD) across a 36-year period 56 reported a very low risk of bleeding (0.6%). This study identified worse liver function (higher total bilirubin and lower albumin levels) rather than coagulopathy as predictor of bleeding.…”
Section: Percutaneous Liver Biopsymentioning
confidence: 99%
“…A recent large study analyzing 3,357 percutaneous liver biopsies performed with Klatskin needle in patients with liver disease (including advanced CLD) across a 36-year period 56 reported a very low risk of bleeding (0.6%). This study identified worse liver function (higher total bilirubin and lower albumin levels) rather than coagulopathy as predictor of bleeding.…”
Section: Percutaneous Liver Biopsymentioning
confidence: 99%
“…Currently, percutaneous liver biopsy is the standard of reference for clinical assessment of hepatic fibrosis [3,4]. However, it is invasive and may cause complications because of puncture, although the assessment is accurate [5]. A reliable noninvasive technique is needed for detecting and staging fibrosis as well for as evaluating treatment response [6].…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the interest in our recent manuscript (1) by Ayubi et al (2) and are grateful for the opportunity to respond.…”
Section: Sirsmentioning
confidence: 89%
“… The authors’ declarations of personal and financial interests are unchanged from those in the original article(1). …”
mentioning
confidence: 99%